MATHEMATICAL MODELING AND OPTIMAL CONTROL OF ABSTAINING ATTITUDE OF COULD COMPUTING ADOPTION. (2021) - M'RHAOUARH, IBTISSAM; ∗, ∗; MOUTAMANNI, HAJAR; LABZAI, ABDERRAHIM; NAMIR, ABDELWAHED; CHAFIQ, NADIA
No abstract available